2019
DOI: 10.3390/s19071485
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Satellite, Unmanned Aerial Vehicle (UAV) and Ground Inversion of the SPAD of Winter Wheat in the Reviving Stage

Abstract: Chlorophyll is the most important component of crop photosynthesis, and the reviving stage is an important period during the rapid growth of winter wheat. Therefore, rapid and precise monitoring of chlorophyll content in winter wheat during the reviving stage is of great significance. The satellite-UAV-ground integrated inversion method is an innovative solution. In this study, the core region of the Yellow River Delta (YRD) is used as a study area. Ground measurements data, UAV multispectral and Sentinel-2A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…Although a comparison with ground truths calculated with a spectroradiometer would have been more effective, a test on compatibility between Sequoia and S2 data is also of scientific relevance, given the growing interest in the integration of data acquired from satellite and UAV platforms [48] for environmental applications [49,50], including PA [51][52][53], both from research and applied points of view.…”
Section: Radiometric Consistency Assessmentmentioning
confidence: 99%
“…Although a comparison with ground truths calculated with a spectroradiometer would have been more effective, a test on compatibility between Sequoia and S2 data is also of scientific relevance, given the growing interest in the integration of data acquired from satellite and UAV platforms [48] for environmental applications [49,50], including PA [51][52][53], both from research and applied points of view.…”
Section: Radiometric Consistency Assessmentmentioning
confidence: 99%
“…Second, the centers of areas with relatively uniform vegetation coverage were selected as sampling points so that vegetation factors could be taken into account during the remote sensing inversion. Furthermore, the survey found that the vegetation in the study area differed significantly under different salinization levels; thus, the vegetation cover could also be used as an indirect indicator in soil salinity monitoring [44][45][46].…”
mentioning
confidence: 99%
“…For example, [69] illustrated the superiority of the RF algorithm compared to SVM and A-NNs for leaf area index retrieving. Similarly, several regression methods such as random forest (RF) [70], and support vector regression (SVR) [12] have been used on UAV imagery.…”
Section: Machine Learning and Statistical Modelsmentioning
confidence: 99%
“…As shown, most studies pertaining to UAV imagery for agro-environmental monitoring are mainly located in North America, Asia, and Europe. Countries with more than ten studies are China (45), United States (26), Canada (13), Italy (12), and Germany (11). In addition, Australia (9), Finland (9), Spain (6), Netherlands (5), Japan (5), South Africa (4), and Brazil 4 Figure 6 illustrates the worldwide distribution of the 39 countries represented.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation